THE QUALITY OF EARNINGS-GENERATING ASSETS, THIRD-PARTY FUNDS, THE BI 7-DAY REPO RATE, AND FINANCIAL SUSTAINABILITY AS DETERMINANTS OF PROFITABILITY IN SHARIA COMMERCIAL BANKS: EMPIRICAL EVIDENCE FROM Q1 2018 TO Q3 2025 - Fania Eka Bella Afifa; Tiara Juliana Jaya (NISBAH: Jurnal Perbankan Syariah, 2026)
The profitability of Islamic commercial banks (BUS) in Indonesia remains relatively low and tends to lag behind that of conventional banks, even though asset and financing growth show a positive trend. This study aims to analyze the influence of the Quality of Earning Assets (QEA), Third-Party Funds (TPF), the BI 7-Day Repo Rate (BI7DRR), and the Financial Sustainability Ratio (FSR) on the profitability of ISBs, as proxied by Return on Assets (ROA). The study employs a descriptive quantitative approach using panel data from 9 ISBs over the period 2018.Q1–2025.Q3, yielding 279 observations. The sample was selected using purposive sampling and analyzed via panel data regression with a Random Effects model determined based on the Chow, Hausman, and Lagrange Multiplier tests. The results indicate that KAP, TPF, and FSR have a significant positive effect on ROA, while BI7DRR has no significant effect. Simultaneously, all independent variables have a significant effect, explaining 51.9% of the variation in ROA. This study contributes by integrating the FSR variable which has rarely been studied into the Islamic banking profitability model, and demonstrates that internal factors are more dominant than external monetary policy in influencing the financial performance of Islamic banks.